ARDUINO UNO ASSISTED EGG STACKER AND COUNTER DESIGN: (Case Study of Lubuk Alung Padang Pariaman Laying Chicken Farm) - BUSRAN; Zulkarnaini; Agung Gunawan (ITP Press, 2023)
The increasing public demand for chicken eggs has made chicken farming a business opportunity that many people are starting to look at. For now, chicken farmers, especially in the Kampung Baru Pungguang Kasiak Lubuk Alung area, Padang Pariaman Regency, West Sumatra, in collecting chicken eggs still use a manual method, namely by picking them up one by one from a chicken coop with an area of 50m x 8m, after which the eggs are then arranged in an egg holder, this is not effective and efficient in terms of time utilization. In this study, an egg collecting and arranging device will be designed to make it easier for farmers to harvest eggs, controlling it using Arduino Uno, infrared sensors, stepper motors, and limit switches. The results of the test on this tool are carried out by means of a tool that can arrange 30 eggs in a container automatically, then when the container is fully loaded, the container will stop automatically.